2020
DOI: 10.1097/md.0000000000023070
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic characteristics of thyroid metastasis from clear cell renal cell carcinoma

Abstract: Introduction: Thyroid metastasis from clear cell renal cell carcinoma (ccRCC) is a very rare condition, and its ultrasonographic characteristics have not been summarized in the literature. We herein report a case of thyroid metastasis from ccRCC that occurred 11 years after the surgery and the ultrasonographic characteristics of it are described. Patient concerns: A 57-year-old male patient was admitted to our hospital in September 2018 due to discomfort in the neck. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In this study, we retrospectively analyzed the ultrasound features of thyroid nodules in three patients with postoperative thyroid metastases from ccRCC ( Table 1 ). We searched PubMed for articles published between 2012 and 2022 on thyroid metastasis from ccRCC, of which eight provided clear ultrasound images and summarized the ultrasound characteristics of the cases mentioned in the eight articles as shown in Table 2 ( 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ). The results showed that thyroid metastasis from ccRCC mostly appeared as a single solid or partially cystic nodule with clear borders, usually without calcification, and with abundant internal blood flow signals.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we retrospectively analyzed the ultrasound features of thyroid nodules in three patients with postoperative thyroid metastases from ccRCC ( Table 1 ). We searched PubMed for articles published between 2012 and 2022 on thyroid metastasis from ccRCC, of which eight provided clear ultrasound images and summarized the ultrasound characteristics of the cases mentioned in the eight articles as shown in Table 2 ( 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ). The results showed that thyroid metastasis from ccRCC mostly appeared as a single solid or partially cystic nodule with clear borders, usually without calcification, and with abundant internal blood flow signals.…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis to the head and neck is less frequent; furthermore, thyroid metastasis is rare (6). ccRCC has previously been reported to metastasize to normal thyroid tissue (7) or benign thyroid tumors (8). However, thyroid metastasis of ccRCC combined with papillary thyroid carcinoma (PTC) is rarely reported.…”
Section: Introductionmentioning
confidence: 99%